Analisis Proses Laser Cutting dengan Variasi Cutting Speed, Jarak Focusline, dan Gas Pressure Terhadap Kekerasan dan Kekasaran Material MS SPHC - Nugraha, Aditya; Pradana, Ilham Wahyu; Nugroho, Yohanes; Nugroho, Adi (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
Laser cutting is a sheet metal cutting technology using laser media combined with a CNC system. The problems of the laser cutting process are defects in the surface of the cutting product caused by a mismatch of parameter variations. The parameters of laser cutting in this research are cutting speed, focusing distance, and gas pressure. Variations in the cutting speed parameters studied were 1440 m/min, 1620 m/min, and 1800 m/min. The variations in the focusing distance studied were 5.5 mm, 6.0 mm, and 6.5 mm. Variations in the gas pressure parameters used are 0.5 bar, 0.7 bar, and 0.9 bar. The Taguchi method is used to obtain variations with minimum hardness and surface roughness values of the material. Surface roughness was tested using a surface roughness tester; surface hardness was tested using a brine hardness tester. The magnitude of the influence of each parameter is analyzed using the ANOVA method. The results showed that the focusing distance parameter had the most significant effect on surface roughness, with a percentage of 50.385%, and the gas pressure parameter was the most influential parameter on surface hardness, with a percentage of 54.241%. The minimum roughness value can be achieved with a cutting speed of 1800 m/min, focusing of 5.5 mm, and gas pressure of 0.5 bar. The minimum hardness value is achieved with a cutting speed of 1800 m/min, a focusing of 6.5 mm, and a gas pressure of 0.5 bar.